Credit management and default of Banco Pichincha del Perú, period 2019 - Hinostroza Hermoza, Henry (2021)
Objective: To determine the incidence of credit management in the delinquency of the microfinance area of ​​Banco Pichincha del Peru during the year 2019, considering information and data from the microfinance area of ​​the agency in question. Method: The research was descriptive, transversal, has a quantitative approach, a non-experimental design, and a quantitative scope. The sample was made up of 124 overdue loans granted by the microfinance area of ​​Banco Pichincha del Peru, during the period of 2019. Results: The investigation’s results show a significant incidence of credit management on delinquencies, finding that 9,12% of the credits approved by the microfinance area are in arrears. Likewise, considering credit management, there is a negative correlation of -0,113 in terms of credit evaluation, and in the same way, a negative correlation of -0,023 in terms of credit conditions. Conclusion: It is concluded that credit conditions have a significant impact on delinquency in the microfinance area of ​​Banco Pichincha del Peru, showing a negative correlation degree of -0,027.